Assessment of hypothermia in the immediate postoperative period - Juliana Mara Gotardo; Cristina Maria Galvão (Rev Rene)
Hypothermia is a common event in the perioperative period. This study aimed to identify the frequency of hypothermia in adult patients in the immediate postoperative period and the nursing interventions implemented in its treatment in the post-anesthesia recovery room (PARR). For data analysis, an instrument was organized and then subject to apparent and content validation. The sample consisted of 30 patients who were followed up since their arrival in the unit until hospital discharge. The average body temperature of patients when arriving at PARR was 35.5ºC. 66% of the investigated patients presented hypothermia. The use of wool blankets with cotton bed sheets was the passive cutaneous warming method most used by the nursing team, and only 6.7% of the patients used the forced-air warming system, a method asserted by the literature as effective in the treatment of hypothermia in the immediate postoperative period.